Evaluation of Hepatoprotective Effects of Coccinia grandis Linn. Against Carbon Tetrachloride Induced Liver Damage in Wistar Rat - VRUSHABENDRA SWAMY, B.M.; KUMAR, G.S.; SHIVA KUMAR, S.I.; SURESH, H.M.; RAJASHEKAR, U.; SREEDHAR, C. (Asian Journal of Chemistry, 2010)
The fruits of Coccinia grandis Linn. are used by the tribes of Karnataka, for the treatment of various hepatic disorders. In the present study, the effect of the methanolic extract of Coccinia grandis Linn. fruits on carbon tetrachloride (CCl4)-induced liver damage in Wistar rats was studied. The results showed that significant hepatoprotective effect was obtained against CCl4-induced liver damage, by oral administration of Coccinia grandis Linn methanolic extract as evident from decreased levels of serum enzymes in the treated groups, compared to the controls. Thus, the present study provides a scientific rationale for the traditional use of this plant in the management of liver diseases.